Molecular evidence for the taxonomic status of Hemidactylus brookii group taxa (Squamata: Gekkonidae) - Bauer, Aaron M.; Jackman, Todd R.; Greenbaum, Eli; Anslem, de Silva; Giri, Varad B.; Indraneil, Das (British Herpetological Society, 2010)
Hemidactylus brookii has one of the widest distributions and, arguably, one of the most confused taxonomic histories of any gekkonid lizard. Nuclear (RAG1 and PDC) and mitochondrial (ND2, cyt b ) DNA sequence data were employed to examine relationships among a sample of putative H. brookii , including a topotypical specimen from Borneo. Two clades were recovered, one consisting of specimens from Borneo (Sarawak), Myanmar, Peninsular Malaysia and Karnataka, southwestern India, and another of specimens from Sri Lanka, Mauritius and Kerala, southwestern India. Both clades are well supported and deeply divergent from one another, whereas genetic variation within each clade is limited. None of the analytical approaches used recovered a well-supported monophyletic H. brookii sensu lato . Near uniformity of H. brookii sensu stricto in East Asia suggests that this species has spread to this region relatively recently. The name H. parvimaculatus Deraniyagala 1953 is available for the Sri Lankan clade and this form should be treated as a valid species. Existing data cannot be used to distinguish whether this species has colonized Sri Lanka from South India or vice versa. The Palghat Gap provides a candidate barrier to gene flow between H. brookii and H. parvimaculatus . Although the identity of H. brookii complex geckos in East Asia and Sri Lanka appears resolved, the situation in India and Pakistan remains complex and thorough revisionary work, coupled with phylogenetic studies, is needed to determine species boundaries in this region